Forecasting Impact of Demand Side Management on Malaysia’s Power Generation using System Dynamic Approach - Tufail, Muhammad Mutasim Billah; Nawi, Mohd Nasrun Mohd; Ali, Akhtiar; Baharum, Faizal; Tahir, Mohamad Zamhari; Salameh, Anas Abdelsatar Mohammad (International Journal of Energy Economics and Policy, 2021)
Rapid economic growth, increasing population, industrialization and high living standards have increased the electricity demand more than ever before. Efficient energy planning and management is always considered as the greatest challenge in all over the world. Among the other factors availability of electricity is the main bottleneck to the economic growth and industrial revolution. Considering this fact, it becomes necessary for academicians, government agencies and electricity companies to construct more efficient methodologies and procedures to predict long-term electricity demand. The objective of this article represents the initiative towards understanding and analyzing the importance of demand-side management (DSM) in forecasting electricity demand by using a system dynamics approach. This study examines the long term impact of demand-side management variables including HER (Home energy report), MEPS (Minimum Energy Performance Standards) and NEEAP (National Energy Efficiency Action Plan). The future installation capacity of Malaysia’s power generation is evaluated considering the factors of population, per capita electricity consumption, efficiency, capacity margin and DSM. The forecasting horizon of the simulation model is 15 years from 2016 to 2030. Keywords: Energy forecasting, System Dynamics, Energy efficiency, Energy Demand Side Management JEL Classifications: O18, Q21 DOI: https://doi.org/10.32479/ijeep.9716